c - L'ENGLE, MADELEINE; MADELEINE L'ENGLE (New York Bantam Doubleday Dell Books for Young Readers, 1986)
follows twins Sandy and Dennys Murry, who accidentally teleport from a cold Connecticut winter to a pre-Biblical Flood desert.
Keywords: the story shifts focus from Meg Murry to her fifteen-year-old twin brothers, Sandy and Dennys; the enduring power of love, the necessity of faith, and the importance of empathy, even in a world filled with conflict and impending destruction